Assessing the Relationship between Technological Factors and the Implementation of Human Resource Information System: A survey in the Municipal, Metropolitan, and District Assemblies in the Upper West Region of Ghana (American Journal of Interdisciplinary Research and Innovation, 2024)
Over the years, public sector organization such as Metropolitan, Municipal, and District Assemblies (MMDAs) in Ghana have been challenged by a significant number of factors that affect the implementation of Human Resource Management Information Systems (HRISs). The study focuses on assessing the technological factors affecting the implementation of the HRIS in the MMDAs in the Upper West Region of Ghana. The philosophical foundation of the study was positivism. A cross-sectional survey was employed in the study as part of a quantitative research design. The target population comprised of 187 Line managers. The study used a non-probability sampling technique known as purposive sampling. Self-administered questionnaires were used to collect primary data. The study also embraced descriptive and inferential statistics. Bivariate regression analysis and correlation coefficient were used to establish causal relationships between variables. Stepwise regression was also used to determine the most influential variables in implementing of HRIS. It was concluded that IT Infrastructure and Compatibility had a moderate level of acceptance as factors that affect the implementation of the HRIS. In contrast, Quality Information, System Quality, and Complexity had a low level of acceptance. The study also concluded that Complexity, Quality Information, Compatibility and System Quality had correlated with the acceptance of the HRIS, whereas IT infrastructure did not correlate with the acceptance of the HRIS. Lastly, it was concluded that IT Infrastructure, Complexity, Quality Information, Compatibility, and System Quality did correlate with the Effectiveness of the HRIS. The study recommends that, HRIS Software adopted and implemented at the LGS and its Agencies must be user-friendly. The LGS and its Agencies do not have a guide that support new technology implementation such as the HRIS. Hence the need to adopt the guide offered in this study.